2013
DOI: 10.3325/cmj.2013.54.17
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial and Y-chromosomal profile of the Kazakh population from East Kazakhstan

Abstract: AimTo study the genetic relationship of Kazakhs from East Kazakhstan to other Eurasian populations by examining paternal and maternal DNA lineages.MethodsWhole blood samples were collected in 2010 from 160 unrelated healthy Kazakhs residing in East Kazakhstan. Genomic DNA was extracted with Wizard® genomic DNA Purification Kit. Nucleotide sequence of hypervariable segment I of mitochondrial DNA (mtDNA) was determined and analyzed. Seventeen Y-short tandem repeat (STR) loci were studied in 67 samples with the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 21 publications
4
17
0
Order By: Relevance
“…S6). Although MJS genome has high heterozygosity, all of the methods employed hint higher Kazakh (including MJS) genetic affinity to East Asians (Mongolian) than Caucasians as previously reported (Tarlykov et al 2013).…”
Section: K=8supporting
confidence: 53%
“…S6). Although MJS genome has high heterozygosity, all of the methods employed hint higher Kazakh (including MJS) genetic affinity to East Asians (Mongolian) than Caucasians as previously reported (Tarlykov et al 2013).…”
Section: K=8supporting
confidence: 53%
“…Tarlykov et al investigated the hypervariable segment I of mitochondrial DNA and Y-STR loci in DNA samples of individuals living in isolation in the same area and who were members of the same tribe. However, there was no comparative analysis with other groups living in other regions of Kazakhstan or who were representatives of other tribes and Zhuzes [19].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies based on Y-STR haplotypes have also demonstrated that the Kalmyks, Mongols, Altaian Kazakhs and Altaians-Kizhi showed a similar haplotype composition, resulting probably from common origin of populations. 6,62 Anthropologists have suggested that in the last 200-300 years, the Kalmyk tribes have experienced some admixture with neighboring East European populations. 63 However, comparison of haplotypes belonging to haplogroups R1a1a-M17 and N1c-Tat, which are frequently occurred in East European populations, shows a low level of East European admixture in the Kalmyks.…”
Section: Discussionmentioning
confidence: 99%